An Insulin-like Growth Factor-1 Conjugated Bombyx mori Silk Fibroin Film for Diabetic Wound Healing: Fabrication, Physicochemical Property Characterization, and Dosage Optimization In Vitro and In Vivo - Meng-Jin Lin; Mei-Chun Lu; Yun-Chen Chan; Yu-Fen Huang; Hwan-You Chang (MDPI AG, 2021)
This study aimed to develop a silk fibroin (SF)-film for the treatment of chronic diabetic wounds. Silk fibroin was purified through a newly developed heating degumming (HD) process and casted on a hydrophobic surface to form SF-films. The process allowed the fabricated film to achieve a 42% increase in transparency and a 32% higher proliferation rate for BALB/3T3 fibroblasts compared to that obtained by conventional alkaline degumming treatment. Fourier transform infrared analysis demonstrated that secondary structure was retained in both HD- and alkaline degumming-derived SF preparations, although the crystallinity of beta-sheet in SF-film after the HD processing was slightly increased. This study also investigated whether conjugating insulin-like growth factor-1 (IGF-1) would promote diabetic wound healing and what the optimal dosage is. Using BALB/3T3 cells grown in hyperglycemic medium as a model, it was demonstrated that the optimal IGF-1 dosage to promote the cell growth was approximately 0.65 pmol. Further analysis of wound healing in a diabetic mouse model indicated that SF-film loaded with 3.25 pmol of IGF-1 showed significantly superior wound closure, a 13% increase at the 13th day after treatment relative to treatment with 65 pmol of free IGF-1. Improvement in diabetic wound healing was exerted synergistically by SF-film and IGF-1, as reflected by parameters including levels of re-epithelialization, epithelial tissue area, and angiogenesis. Finally, IGF-1 increased the epithelial tissue area and micro-vessel formation in a dose-dependent manner in a low dosage range (3.25 pmol) when loaded to SF-films. Together, these results strongly suggest that SF-film produced using HD and loaded with a low dosage of IGF-1 is a promising dressing for diabetic wound therapy.